Wage rigidity, collective bargaining and the minimum wage: Evidence from French agreement data - Sanvi Avouyi-Dovi; Denis Fougère; Erwan Gautier (Institute for the Study of Labor (IZA), 2011)
Using several unique data sets on wage agreements at both industry and firm levels in France, we document stylized facts on wage stickiness and the impact of wage-setting institutions on wage rigidity. First, the average duration of wages is a little less than one year and around 10 percent of wages are modified each month by a wage agreement. Data patterns are consistent with predictions of a mixture of Calvo and Taylor models. The frequency of wage change agreements is rather staggered over the year but the frequency of effective wage changes is seasonal. The national minimum wage has a significant impact on the probability of a wage agreement and on the seasonality of wage changes. Negotiated wage increases are correlated with inflation, the national minimum wage increases and the firm profitability.
urn:nbn:de:101:1-201107133482
Keywords: J31; J50; E30; 330; wage stickiness; wage bargaining; minimum wage; downward nominal wage rigidity